Camarillo State Hospital - Camarillo, California - Camarillo State, Hospital (Camarillo State Hospital)
Camarillo State Hospital is a mental health center treating all ages and all categories of mental disorders. Note: Due to the complex nature of the printing style in this document, it cannot be made compliant for the seeing impaired. Please contact the archivist for other accommodations.